Coronavirus disease 2019 (COVID-19): NETosis-associated mechanisms of progression and prospects for therapy regulating the formation of neutrophil extracellular traps (NETs) - K. A. Aitbaev (Scientific Сentre for Family Health and Human Reproduction Problems, 2021)
Infectious disease COVID-19 caused by the SARS-CoV-2 coronavirus is characterized by high contagiousness, complexity of pathogenesis and unpredictability of the clinical course. In severe cases, which are especially susceptible to men, the elderly and people with underlying medical conditions such as obesity, diabetes, hypertension, cardiovascular and chronic respiratory diseases, the infection leads to respiratory failure and death due to the development of an extensive inflammatory reaction. As a result of many studies, it has been established that one of the leading causes of the severe course and death of patients with COVID-19 is the development of coagulopathy, that is, increased thrombus formation in small vessels due to excessive activity of neutrophils, which form the so-called neutrophil extracellular traps (NETs). Although NETs play a useful role in protecting their host from pathogens, their overgrowth can trigger a cascade of adverse reactions including: the production of antibodies against the host’s DNA (autoimmunization); damage to surrounding tissue; or the occurrence of thromboembolic complications. Therefore, extracellular neutrophil traps and their markers have been identified as targets for new therapeutic strategies aimed at reducing the severity of COVID-19 disease and/or mortality. This article describes the structure of NETs, as well as analyzes the molecular mechanisms that contribute to their overgeneration. In addition, the prospects for COVID-19 therapy aimed at regulating the formation of extracellular traps by creating drugs both limiting the production of NET structures and dissolving their excess amounts in the body of patients are discussed.